Evaluasi Retakan Pada Pekerjaan Core Wall - Judiono (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2025)
During concrete construction, it is essential to ensure that the casting outcomes are both dense and uniform in composition. However, in the field implementation, there are often cracks in the surface of the concrete from the casting, which is known after the dismantling of the casting. The type and condition of cracks that arise on the concrete surface can be distinguished; cracks due to dropping, drying shringkage cracking, concrete crazing, thermal cracking, map cracking The existence of these cracks can affect the strength and functionality of the structure. This study is intended to identify the condition of cracks with quantitative methods, whether the cracks that arise are structurally dangerous and how to handle them. The results of the data calculation show that the cracks are still within tolerance to the strength of the construction, but improvements need to be made so that they are still aesthetically qualified. Thus, from the results of the analysis, it can be ascertained that the construction even though cracks arise are still suitable for function because the cracks that arise are not dangerous based on structural calculations.